2016
DOI: 10.1371/journal.pone.0162219
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Potato Crop Yield Using Precision Agriculture Techniques

Abstract: Crop growth and yield monitoring over agricultural fields is an essential procedure for food security and agricultural economic return prediction. The advances in remote sensing have enhanced the process of monitoring the development of agricultural crops and estimating their yields. Therefore, remote sensing and GIS techniques were employed, in this study, to predict potato tuber crop yield on three 30 ha center pivot irrigated fields in an agricultural scheme located in the Eastern Region of Saudi Arabia. La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
102
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(109 citation statements)
references
References 17 publications
4
102
0
3
Order By: Relevance
“…Immitzer et al [23] confirmed the expected capabilities for producing reliable land cover maps in Central Europe at 10 m spatial resolution using pre-operational (August 2015) single date Sentinel-2 data. Al-Gaadi et al [24] used a single date Sentinel-2 image of early 2016 for potato yield prediction in irrigated fields in Saudi Arabia using an empirical relationship with vegetation indices. To our knowledge this is the first paper deriving agricultural crop variables from multi-date Sentinel-2 images.…”
Section: Discussionmentioning
confidence: 99%
“…Immitzer et al [23] confirmed the expected capabilities for producing reliable land cover maps in Central Europe at 10 m spatial resolution using pre-operational (August 2015) single date Sentinel-2 data. Al-Gaadi et al [24] used a single date Sentinel-2 image of early 2016 for potato yield prediction in irrigated fields in Saudi Arabia using an empirical relationship with vegetation indices. To our knowledge this is the first paper deriving agricultural crop variables from multi-date Sentinel-2 images.…”
Section: Discussionmentioning
confidence: 99%
“…In the last years many studies have focused on the use of medium resolution satellite data (10-100 m) for yield estimation at broader spatial resolution (local, regional, country scales) even for long-term yield series analysis [20][21][22][23][24][25][26]. While studies are conducted by the use of very high resolution imagery [27][28][29][30] to identify within-field variability of crop growth and yield and for the definition of management zones, few [31] have used Sentinel-2 to provide an insight into field productivity variation for better future management [32][33][34]. The objectives of this study were to:…”
Section: Introductionmentioning
confidence: 99%
“…Potato (Solanum tuberosum L.) is one of the most important field crops in Saudi Arabia because of its role in providing food and proteins (Hadi, 2012). Average yields vary between 21 and 40 t ha -1 (Al-Gaadi et al, 2016). Increased mechanization was one of the most influential factors in the ability to expand potato production and minimize the production cost, thus increasing the net income for potato producers (Al-Dosary, 2016).…”
Section: Introductionmentioning
confidence: 99%